Risk of Coronary Obstruction and Feasibility of Coronary Access After Repeat Transcatheter Aortic Valve Replacement With the Self-Expanding Evolut Valve: A Computed Tomography Simulation Study. (December 2020) - Forrestal, Brian J.; Case, Brian C.; Yerasi, Charan; Shea, Corey; Torguson, Rebecca; Zhang, Cheng; Ben-Dor, Itsik; Deksissa, Teshome; Ali, Syed; Satler, Lowell F.; Shults, Christian; Weissman, Gaby; et al.
Abstract : Background: The supra-annular leaflet position and tall stent frame of the self-expanding Evolut PRO or Evolut PRO+ transcatheter heart valves (THVs) may cause coronary occlusion during transcatheter aortic valve replacement (TAVR)-in-TAVR and present challenges for future coronary access. We sought to evaluate the risk of TAVR-in-TAVR with Evolut PRO or Evolut PRO+ THVs and the feasibility of future coronary access. Methods: The CoreValve Evolut PRO Prospective Registry (EPROMPT; NCT03423459) prospectively enrolled patients with symptomatic severe aortic stenosis to undergo TAVR using a commercially available latest generation self-expanding THV at 2 centers in the United States. Computed tomography was performed 30 days after TAVR, which we used to simulate TAVR-in-TAVR with a second Evolut PRO or Evolut PRO+ THV and evaluate for risk of coronary obstruction and feasibility of future coronary access. Results: Eighty-one patients enrolled with interpretable computed tomography are reported herein. Computed tomography simulation predicted sinus of Valsalva sequestration and resultant coronary obstruction during future TAVR-in-TAVR in up to 23% of patients. Computed tomography simulation predicted that the position of the pinned THV leaflets would hinder future coronary access in up to 78% of patients after TAVR-in-TAVR. Conclusions: Further THV design improvements and leaflet modification strategies are needed to mitigate the risk of coronary obstruction during TAVR-in-TAVR with self-expanding THVs and to facilitate future coronary access. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03423459. Abstract : Supplemental Digital Content is available in the text.